The effect of Iran’s health sector evolution plan on hospitals performance indicators: an interrupted time series analysis - Soltani, Shahin; Rezaei, Satar; Kazemi-Karyani, Ali; Azimi, Jila; Jalili, Faramarz; Roshani, Bahman; Najafi, Farid; Bagheri, Parnia; Salimi, Yahya (Frontiers in Health Services, 2023)
Background The Health Sector Evolution Plan (HSEP) was set up in Iran’s health system to respond to some of the main problems in hospitals and other health sectors. We aimed to compare the effect of the HSEP on teaching hospital performance before and after the implementation of the HSEP through the interrupted time series (ITS) analysis. Methods With a cross-sectional design, data collection was performed in 17 teaching hospitals affiliated with the Kermanshah University of Medical Sciences (KUMS). We used the existing data on three indicators of hospitalization rate (per 10,000 population), Emergency Department Visits (EDVs) (per 10,000 population), and in-hospital mortality (per 10,000 population). The monthly data from 2009 to 2019 was analyzed by the ITS method 60 months before and 61 months after the HSEP. Results We found a non-statistically significant decrease in the monthly trend of hospitalization rate relative to the period before the HSEP implementation (−0.084 per 10,000 population [95%CI: −0.269, 0.101](. There was a statistically significant increase in the monthly trend of EDVs rate compared to before the HSEP implementation (1.07 per 10,000 population [95%CI: 0.14, 2.01]). Also, a significant decrease in the monthly trend of in-hospital mortality compared to before the HSEP implementation [−0.003 per 10,000 population (95%CI: −0.006, −0.001)] was observed. Conclusion Our study demonstrated a significant increasing and decreasing trend for EDVs and in-hospital mortality following the HSEP implementation, respectively. Regarding the increase in hospitalization rate and EDVs after the implementation of HESP, it seems that there is a need to increase investment in healthcare and improve healthcare infrastructure, human resources-related indicators, and the quality of healthcare.